Comprehensive Physiology 2011
DOI: 10.1002/cphy.c100039
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of Endothelin and the Kidney

Abstract: Since its discovery in 1988 as an endothelial cell-derived peptide that exerts the most potent vasoconstriction of any known endogenous compound, endothelin (ET) has emerged as an important regulator of renal physiology and pathophysiology. This review focuses on how the ET system impacts renal function in health; it is apparent that ET regulates multiple aspects of kidney function. These include modulation of glomerular filtration rate and renal blood flow, control of renin release, and regulation of transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
136
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(140 citation statements)
references
References 492 publications
(788 reference statements)
4
136
0
Order By: Relevance
“…The diuretic response following intramedullary infusion of hyperosmotic saline was attenuated by dual blockade of ET A and ET B receptors (7), suggesting that infusion of hyperosmotic saline to the renal medulla results in ET-dependent diuresis (7). This is in line with accumulating evidence highlighting a central role for renal medullary derived ET-1 in the control of renal excretory function (6,7,14,15,17,21,26). …”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The diuretic response following intramedullary infusion of hyperosmotic saline was attenuated by dual blockade of ET A and ET B receptors (7), suggesting that infusion of hyperosmotic saline to the renal medulla results in ET-dependent diuresis (7). This is in line with accumulating evidence highlighting a central role for renal medullary derived ET-1 in the control of renal excretory function (6,7,14,15,17,21,26). …”
Section: Discussionsupporting
confidence: 58%
“…Our studies also revealed an inhibitory effect of combined blockade of ET A and ET B receptors on the diuretic and natriuretic effect of UTP. We used the approach of blocking both receptor subtypes given evidence that both ET A and ET B receptors could participate in ET-1-dependent natriuresis even though the predominant action is via the ET B receptor (15,29). Use of selective ET B receptor antagonists has the unfortunate consequence of increasing ET A receptor activity, which would make interpretation of such results problematic.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that ET A receptor blockade may contribute to fluid retention by the kidney (Stuart et al, 2013), but it is not clear whether this accounts for the fluid retention issues in human trials. It is certainly possible that these drugs have some unexpected degree of ET B receptor blockade in humans, especially those with susceptibility to fluid retention, because the ET B receptor clearly facilitates sodium excretion (Kohan et al, 2011a). They have now conducted two successful phase 2 studies that demonstrate manageability of the fluid retention issue (Kohan et al, 2011b;de Zeeuw et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…ET-1 plays a crucial role in the regulation of physiological smooth muscle motility, [1][2][3] but ET-1 is also implicated in a large variety of pathologies, including hypertension, heart failure, kidney disorders and infectious diseases. [4][5][6] In addition, the ET axis is overexpressed in cancer of different organs contributing to tumor growth by acting on cell proliferation, survival, migration, differentiation, angiogenesis and inflammatory cell recruitment. 7,8 ETA are upregulated in prostate, 9 ovary 10 and breast cancers while ETB is overexpressed in melanoma.…”
Section: Introductionmentioning
confidence: 99%